RITUAL PUASA DALAM ISLAM Analisis Sosial dengan teori rites de passage Arnold van Gennep - Agus Purnomo (Studia Philosophica et Theologica, 2007)
There is a similar religious ritual activity which can be found in various religious traditions. However, those ritual activities have uniqueness related to local articulation as well as their built construction on it. Although they are differently articulated and practiced, they generally have almost the same meaning. This phenomenon indicates that religions substantially pose similar life orientation namely reaching the goodness now and hereafter. Rites de passage analysis seems to be wise alternative analysis to look at deeply the Muslim religious reality namely “fasting”. Based on this theoretical context, fasting can be discussed in three phases, they are; separation, liminality, incorporation. Each phase has deep meaning for Muslim because it touch not only Muslim’s theological belief but also their social dimension in terms of various happiness expression to welcome and to fulfill the blessing month with pious activities. These all religious practices aim to reach “piety” as new predicate for all people after passing the phase.